Associations Between Disordered Microbial Metabolites and Changes of Neurotransmitters in Depressed Mice - Xie, Jing; Wang, Ying; Zhong, Qi; Bai, Shun-jie; Zhou, Chan-juan; Tian, Tian; Chen, Jian-jun (Frontiers in Cellular and Infection Microbiology, 2022)
Backgrounds: Many evidences demonstrated that there were close relationships between gut microbiota and depression. But the specific molecular mechanisms were still unknown. Here, using targeted metabolomics, this study was conducted to explore the relationships between microbial metabolites in feces and neurotransmitters in prefrontal cortex of depressed mice. Methods: Chronic unpredictable mild stress (CUMS) model of depression was built in this study. Targeted liquid chromatography-mass spectrometry (LC-MS) analysis was used to detect the microbial metabolites in feces and neurotransmitters in prefrontal cortex of mice. Both univariate and multivariate statistical analyses were applied to identify the differential microbial metabolites and neurotransmitters and explore relationships between them. Results: 98 differential microbial metabolites (mainly belonged to amino acids, fatty acids, and bile acids) and 11 differential neurotransmitters (belonged to tryptophan pathway, GABAergic pathway and catecholaminergic pathway) were identified. Five affected amino acids-related metabolic pathways were found in depressed mice. The 19 differential microbial metabolites and 10 differential neurotransmitters were found to be significantly correlated with depressive-like behaviors. The two differential neurotransmitters (tyrosine and glutamate) and differential microbial metabolites belonged to amino acids had greater contributions to the overall correlations between microbial metabolites and neurotransmitters. In addition, the significantly decreased L-Tyrosine as microbial metabolites and tyrosine as neurotransmitter had the significantly positive correlation (r=0.681, p=0.0009). Conclusions: These results indicated that CUMS-induced disturbances of microbial metabolites (especially amino acids) might affect the levels of neurotransmitters in prefrontal cortex, and then caused the onset of depression. Our finds could broaden the understanding of how gut microbiota was involved in the onset of depression.